2022
DOI: 10.1186/s12888-022-04367-3
|View full text |Cite
|
Sign up to set email alerts
|

The 14-item short health anxiety inventory (SHAI-14) used as a screening tool: appropriate interpretation and diagnostic accuracy of the Swedish version

Abstract: Background The 14-item Short Health Anxiety Inventory (SHAI-14) is a common measure of health anxiety but its screening properties have not been studied. The aims of this study were to evaluate the SHAI-14 as a screening instrument, identify cut-offs for clinically significant health anxiety and investigate which scores correspond to different severity levels. Method The study included 1729 psychiatric patients and 85 healthy controls. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…A clinical study demonstrated that individuals with elevated health anxiety tend to be more preoccupied with the emotional impact of the health condition than individuals with normal levels of health anxiety [42]. Other results conclude that in a clinical sample (patients with a primary psychiatric diagnosis, such as panic disorder, social anxiety disorder, or major depressive disorder) and healthy control sample, different score interpretations may be useful, depending on the specific context and purpose of the scientist in applying the SHAI [31,43].…”
Section: Discussionmentioning
confidence: 98%
“…A clinical study demonstrated that individuals with elevated health anxiety tend to be more preoccupied with the emotional impact of the health condition than individuals with normal levels of health anxiety [42]. Other results conclude that in a clinical sample (patients with a primary psychiatric diagnosis, such as panic disorder, social anxiety disorder, or major depressive disorder) and healthy control sample, different score interpretations may be useful, depending on the specific context and purpose of the scientist in applying the SHAI [31,43].…”
Section: Discussionmentioning
confidence: 98%
“…The primary outcome was a change in health anxiety as measured with the widely used SHAI-14, which has excellent psychometric properties 21 and shows evidence of good diagnostic utility in both clinical and non-clinical settings. 22 Participants completed the SHAI-14 at baseline, each week during treatment, after treatment (week 8), after four additional weeks (week 12) and at the 3-month follow-up (week 24).…”
Section: Methodsmentioning
confidence: 99%
“…The scoring of the scale is between 0 and 3 for each item, and a high score indicates a high level of health anxiety. HAI-SF scores of 0-27 represented no or mild health anxiety, 28-32 moderate health anxiety and 33-42 substantial health anxiety (13,14). The anxiety level of the participants in the last one week were evaluated with the "Beck Anxiety Inventory".…”
Section: Methodsmentioning
confidence: 99%